Production of an educational technology aimed at patients rehabilitation for ankle fractures (Research, Society and Development, 2022)
Educational technologies are important tools in promoting health education and continuity of patient care. The objective of this article was to create an educational booklet aimed at patients undergoing rehabilitation of surgically treated ankle fractures. It was a descriptive study developed in the municipality of Santarém/PA for the production of the booklet, being divided into three phases: bibliographical survey of the literature, preparation of an outline for the development process of the educational technology and final construction of the educational booklet. The booklet created was entitled “Guidelines for rehabilitation of ankle fractures”, consisting of eight specific rehabilitation topics, using language accessible to the target audience, according to the Flesch readability index. In this way, educational booklets can be important mechanisms for the dissemination of scientific information, when well-prepared and visually pleasing. Given the various forms of application, this booklet can help in the rehabilitation process of patients undergoing treatment for ankle fractures.